Quality and satisfaction of house owners for industrialised building system and conventional building system - Mohammad, Hairuddin (2009)
This research was carried out to identify the relationship between quality and satisfaction of house owners for construction systems. Two construction systems will become the dependant variables which is Industrialised Building System (IBS) and conventional system. Additionally, the differences toward quality across years of existence of selected housing areas are taken into consideration. The aim of this study is to collect data by using sets of questionnaires. Then, the correlation analysis are carried out by using Statistical Package for Social Science (SPSS) software and the difference analysis is by using Independent Samples T-Test. The results shows that house owners for both construction systems is highly satisfied with their houses and there is no significant relationship between quality and house owners' satisfaction except for the mechanical and electrical aspect for both construction systems. However, there is a significant relationship between quality across years of existence of selected housing areas. Last but not least, findings from this research may benefited to government agencies such as Construction Industry Development Board (CIDB) and other researchers 377$ especially on development of low cost housing schemes